2018
DOI: 10.5194/esurf-2018-63
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating lateral moraine sediment supply to a debris-covered glacier in the Himalaya

Abstract: Abstract. Debris-covered glacier tongues in the Himalaya play an important role in the high-altitude water cycle. The thickness of the debris layer is a key control of the melt rate of those tongues, yet little is known about the relative importance of the three potential sources of debris supply to those glaciers: the headwalls, the glacier bed or the lateral moraines. In this study we hypothesize that erosion from the lateral moraines is a significant debris supply to the debris-covered tongues, in particula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The increase has happened especially by widening and up-glacier expansion of existing longitudinal debris features, along and next to those glacier regions that are partly fed by avalanches. Potentially relevant amounts of debris input originate from lateral moraines that border Zmuttgletscher and its SBG branch in the lower region of the tongue, but their influence is likely constrained to the glacier margin (van Woerkom et al, 2018). Changes -mainly increase -of debris-covered area have been shown for other Alpine glaciers, the Himalaya, and the Caucasus, but have so far not been quantified for a century-long period: Deline (2005) presented a qualitative description of supraglacial debris evolution for several glaciers in the Mont Blanc region since the 18 th century; Kellerer-Pirklbauer et al (2008) showed that the debris-covered area of Pasterze in Austria increased from 5.4% to 7.3% between 1964 and 2000; Stokes et al (2007) found an increase of 3-6% points at various glaciers in the Russian Caucasus; Gibson et al (2017) found a slight decrease of debris-covered area on Baltoro glacier from 2001-2012; Bhambri et al (2011) found an increase of debris-covered area in the upper Gangotri basin but didn't quantify it.…”
Section: Placing Of Results In a Wider Contextmentioning
confidence: 99%
“…The increase has happened especially by widening and up-glacier expansion of existing longitudinal debris features, along and next to those glacier regions that are partly fed by avalanches. Potentially relevant amounts of debris input originate from lateral moraines that border Zmuttgletscher and its SBG branch in the lower region of the tongue, but their influence is likely constrained to the glacier margin (van Woerkom et al, 2018). Changes -mainly increase -of debris-covered area have been shown for other Alpine glaciers, the Himalaya, and the Caucasus, but have so far not been quantified for a century-long period: Deline (2005) presented a qualitative description of supraglacial debris evolution for several glaciers in the Mont Blanc region since the 18 th century; Kellerer-Pirklbauer et al (2008) showed that the debris-covered area of Pasterze in Austria increased from 5.4% to 7.3% between 1964 and 2000; Stokes et al (2007) found an increase of 3-6% points at various glaciers in the Russian Caucasus; Gibson et al (2017) found a slight decrease of debris-covered area on Baltoro glacier from 2001-2012; Bhambri et al (2011) found an increase of debris-covered area in the upper Gangotri basin but didn't quantify it.…”
Section: Placing Of Results In a Wider Contextmentioning
confidence: 99%